The Not-So-Intelligent Designer Why Evolution Explains the Human Body and Intelligent Design Does Not - Hafer, Abby. (Eugene : Wipf and Stock Publishers, 2015)
Why do men's testicles hang outside the body? Why does our appendix sometimes explode and kill us? And who does the Designer like better, anyway--us or squid? These and other questions are addressed in The Not-So-Intelligent Designer: Why Evolution Explains the Human Body and Intelligent Design Does Not. Dr. Abby Hafer argues that the human body has many faulty design features that would never have been the choice of an intelligent creator. She also points out that there are other animals that got better body parts, which makes the Designer look a bit strange; discusses the history and politics.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 244.
Print version record.
Keywords: Evolution (Biology); Intelligent design (Teleology); Creationism; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; RELIGION / Spirituality; Electronic books